2003
DOI: 10.1200/jco.2003.09.035
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Results of First-Line Sequential High-Dose Etoposide, Ifosfamide, and Cisplatin Chemotherapy Plus Autologous Stem Cell Support for Patients With Advanced Metastatic Germ Cell Cancer: An Extended Phase I/II Study of the German Testicular Cancer Study Group

Abstract: Repetitive cycles of high-dose VIP with peripheral stem cell support can be successfully applied in a multicenter setting. Dose level 6 with cisplatin 100 mg/m2, etoposide 1500 mg/m2, and ifosfamide 10 g/m2 is recommended for further investigation in randomized trials. An ongoing randomized trial within the European Organization for Research and Treatment of Cancer evaluates this protocol against four cycles of standard cisplatin, etoposide, and bleomycin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
71
0
5

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 151 publications
(78 citation statements)
references
References 32 publications
2
71
0
5
Order By: Relevance
“…The results of our retrospective analysis yields results similar to the published matched-pairs analysis 2 and compare favorably with the results of the EORTC 30974 trial 5 and the results presented by Motzer et al 4 The CR rate was 73% after HD-PBSCT and resection of residual disease. With a median follow-up of 51.5 months, survival after 3 years was 79.5% for all patients and 80% for the 40 patients with poor prognosis.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The results of our retrospective analysis yields results similar to the published matched-pairs analysis 2 and compare favorably with the results of the EORTC 30974 trial 5 and the results presented by Motzer et al 4 The CR rate was 73% after HD-PBSCT and resection of residual disease. With a median follow-up of 51.5 months, survival after 3 years was 79.5% for all patients and 80% for the 40 patients with poor prognosis.…”
Section: Discussionsupporting
confidence: 89%
“…The applicated HD chemotherapy regimen HD-PEI was adapted from our previous experience in a large phase I/II trial (dose level 6). 2 In 14 patients we added paclitaxel according to dose level 3 of the phase I/II study by the German Testicular Cancer Study Group. 9 Up to four cycles of HD-chemotherapy were administered according to individual patient's response and tolerability.…”
Section: Treatment Protocolmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior studies of other malignancies have reported an 8-10% cumulative incidence of second malignancies after HDCT/ASCR. [22][23][24][25][26] The intensive chemotherapy used for treatment might induce a second malignancy in patients with a germline predisposition to cancer. In the study conducted by Kleinerman et al, 2 radiation increased the risk of second malignancies in patients with hereditary retinoblastoma, but there was no development of a subsequent malignancy among the hereditary patients treated with conventional chemotherapy alone.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with a primary retroperitoneal NSGCT achieved a 5-year disease-specific survival of 76%, while patients with a mediastinal primary reached 67%. 20 In the EBMT experience with chemotherapeutic regimens including one to four courses of early HDCT after induction chemotherapy, 17 patients (76%) achieved a CR, and 15 (67%) are currently disease-free at a median followup of 50 months (range 26-132). No toxic death occurred and no patient developed myelodysplasia or secondary leukemia after HDCT.…”
Section: Discussionmentioning
confidence: 99%